Entrepreneurial Orientation in the Segment of Micro-Enterprises: Evidence from Czech Republic - Civelek Mehmet; Rahman Ashiqur; Kozubikova Ludmila (International Journal of Entrepreneurial Knowledge, 2016)
The objective of this comprehensive research is to identify and explore the dissimilarities of gender and education level of entrepreneurs and enterprises’ age with regards to entrepreneurial orientation (EO) in the segment of micro enterprises. All of the dimensions of EO are included such as innovativeness, risk taking, proactiveness, competitive aggressiveness and autonomy for our analysis. The data that we have used for this study, was collected by a structured questionnaire during 2015 in Czech Republic, and consists of 1141 small and medium-sized enterprises (SMEs) and 740 of them are defined as micro enterprises by using the definition of European Commission. The empirical results of our study indicates a that university educated micro-entrepreneurs are more innovative and autonomous comparing with lower educated micro-entrepreneurs and also younger micro firms are more innovative, risk taker and proactive than the older micro firms. However, our results do not show any significant differences between men and women in relation to the all components of EO. Our result can be explained by having higher percentage of university educated women micro entrepreneurs comparing with their men counterparts and education may have a substitution effect on the gender based differences in the segment of micro firms.